Inspiratory muscle training to reduce risk of pulmonary complications after coronary artery bypass grafting: a systematic review and meta-analysis - Xiang, Yuping; Zhao, Qin; Luo, Tinahui; Zeng, Ling (Frontiers in Cardiovascular Medicine, 2023)
Background Pulmonary complications occur in a substantial proportion of patients who undergo coronary artery bypass grafting. Inspiratory muscle training (IMT), a simple, well-tolerated physical therapy, has been proposed to reduce risk of complications, but its efficacy remains controversial. Method Randomized controlled trials (RCTs) examining the influence of IMT on risk of pulmonary complications after coronary artery bypass grafting were identified in PubMed, Embase, CENTRAL, CINAL, and Web of Science through March 2023. Data were meta-analyzed for the primery outcomes of pulmonary complications, defined as pneumonia, pleural effusion, and atelectasis; and in terms of the secondary outcomes of maximum inspiratory pressure, maximum expiratory pressure, length of hospitalization, 6-min walk test, and peak expiratory flow and other outcomes. Results Data from 8 RCTs involving 755 patients were meta-analyzed. IMT was associated with significantly lower risk of postoperative pneumonia (RR 0.39, 95% CI 0.25-0.62, P < 0.001) and atelectasis (RR 0.43, 95% CI 0.27-0.67, P < 0.001), but not pleural effusion (RR 1.09, 95% CI 0.62-1.93, P = 0.76). IMT was associated with significantly better maximum inspiratory pressure(preoperative,SMD 16.55 cmH2O;95% CI: 13.86~19.24, P<0.00001), (postoperative,MD 8.99 cmH2O;95% CI: 2.39~15.60, P =0.008) and maximum expiratory pressure (SMD 7.15 cmH2O;95% CI: 1.52~12.79, P =0.01), and with significantly shorter hospitalization (SMD -1.71 days, 95% CI -2.56 to -0.87, P < 0.001). IMT did not significantly affect peak expiratory flow or distance travelled during the 6-min walk test. Conclusions The available evidence from high-quality trials suggests that IMT can significantly decrease risk of pneumonia and atelectasis after coronary artery bypass grafting, while shortening hospitalization and improving the strength of respiratory muscles.